2005
DOI: 10.1002/polb.20471
|View full text |Cite
|
Sign up to set email alerts
|

Effects of guest microparticles on the swelling behavior of polyacrylamide gels

Abstract: We report the effects of guest particles on the swelling properties of bulk polyacrylamide gels. The guest particles were the spheres of poly(N‐isopropylacrylamide) gel with submicrometer diameter, which were synthesized by an emulsion‐polymerized reaction in water. Polyacrylamide gels were prepared by a free radical polymerization reaction, immobilizing the gel microparticles with different concentrations at gelation. The macroscopic swelling ratio of this hybrid gel in a cylindrical shape was measured as fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…Swelling particle (SP): Swelling particles are made of chemical reagents such as monomers, stabilizers, proppants and swelling agents, which are fabricated through crushing and screening after reaction [ 30 , 31 , 32 ]. Compared with CBG, SP not only have the advantage of a high plugging rate, but also have the characteristics of controllable gelling conditions, good temperature resistance and salt resistance [ 33 ]. In the practice of oilfield, SP can be used as the front slug of cross-linked bulk gel and swelling particle system for profile control, which can be used to treat fractured reservoirs with serious water channeling [ 34 , 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…Swelling particle (SP): Swelling particles are made of chemical reagents such as monomers, stabilizers, proppants and swelling agents, which are fabricated through crushing and screening after reaction [ 30 , 31 , 32 ]. Compared with CBG, SP not only have the advantage of a high plugging rate, but also have the characteristics of controllable gelling conditions, good temperature resistance and salt resistance [ 33 ]. In the practice of oilfield, SP can be used as the front slug of cross-linked bulk gel and swelling particle system for profile control, which can be used to treat fractured reservoirs with serious water channeling [ 34 , 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…More detail preparation process for the PPS and other polymer's nanofibers with the CLSD method had been described in the previous articles. 5,6 Polarized IR spectra were observed using JASCO FT-IR 4200 spectrometer to obtain the molecular orientation of the drawn PPS nanofibers at room temperature: measurement range of 4000-500 cm À1 , the spectral resolution of 4.0 cm À1 , and the number of scans of 60.…”
Section: Experimental Section/ Methodsmentioning
confidence: 99%
“…Recently, Suzuki et al have proposed the novel technique to make polymer nanofibers using a high-power carbon dioxide (CO 2 ) laser-based supersonic drawing method in the vacuum chamber, so called as the CLSD method: the drawing velocity is about 300-600 ms À1 . 5 The polymer nanofibers prepared by the CLSD method have characteristic properties with very long filaments and high molecular homogeneous orientation. In the previous article, 6 we showed that the crystallinity of the PPS nanofibers obtained by the CLSD method decreases with increase of the pressure in the chamber (p ch ).…”
Section: Introductionmentioning
confidence: 99%